2008
DOI: 10.1080/14789940801936597
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorder, temperament, and childhood adversity: findings from a cohort of prisoners in England and Wales

Abstract: Adverse childhood experiences and childhood temperamental features are known to contribute to the development of personality disorder. The aim of this study was to examine associations between personality disorder, childhood temperament, adverse childhood experiences, and victimisation. The Prisoner Cohort Study was carried out as part of the dangerous and severe personality disorder (DSPD) service development programme commissioned by the Home Office. The study comprised 1396 male offenders interviewed with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 82 publications
5
20
1
Order By: Relevance
“…Overall, there may be a considerable number of personality disordered individuals within the UK national probation system. Our findings are broadly similar to studies of PD within the UK prison system, which have reported that about 66% to 73% of inmates score positive for any PD (Roberts et al, ; Ullrich et al, ) and also estimates of PD in the prison population worldwide of around 65% (Fazel & Danesh, ). Although our sample size was adequate for a validation study, it did not allow us to examine the prevalence of PD among probationers with any degree of precision and assertions about the overall prevalence of PD in our sample should be made cautiously.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, there may be a considerable number of personality disordered individuals within the UK national probation system. Our findings are broadly similar to studies of PD within the UK prison system, which have reported that about 66% to 73% of inmates score positive for any PD (Roberts et al, ; Ullrich et al, ) and also estimates of PD in the prison population worldwide of around 65% (Fazel & Danesh, ). Although our sample size was adequate for a validation study, it did not allow us to examine the prevalence of PD among probationers with any degree of precision and assertions about the overall prevalence of PD in our sample should be made cautiously.…”
Section: Discussionsupporting
confidence: 90%
“…One might anticipate a high prevalence of PD among the general probation population by extrapolating prevalence estimates from surveys of prisoners (e.g. Roberts, Yang, Zhang, & Coid, 2008;Ullrich et al, 2008). However, individuals supervised by probation services will generally have committed less serious offences than those in prison.…”
Section: Introductionmentioning
confidence: 99%
“…Although drug addiction, poverty and mental illness are leading causes of incarceration (Ludwig et al, ; BJS, , ; Inciardi, ), the inability to cooperate, or to behave in a way that maximises joint ‘payoff’ in lieu of individual gain, may also contribute to both incarceration and recidivism. Indeed, various personality deficits or temperamental traits in line with this have been demonstrated (Egan et al, ; Longato‐Stadler et al, ; Roberts et al, ; Edens, ; Listwan et al, ). There is also evidence that learned cognitive distortions, perhaps from the culture of the criminal justice system, may foster uncooperative behaviour (Walters, ; Bulten et al, ).…”
Section: Introductionmentioning
confidence: 87%
“…Childhood developmental factors are now accepted as having a contributory role in the pathways to offending in adult life (Roberts, Zhang, Yang, & Coid, 2008). A study comparing adult rapists with child molesters across a range of static measures and developmental variables, provided a risk prediction model aimed at distinguishing between sex offenders at highest risk of community treatment failure from those most likely to succeed in treatment.…”
Section: Characteristics Of Juvenile Perpetrators Of Csamentioning
confidence: 99%